Taxonomic notes on Leandra (Melastomataceae, Miconieae) - Reginato,Marcelo (2012)
In this paper we propose 11 synonyms and six lectotypes for eastern Brazilian species of Leandra. Leandra urophylla and L. nutans are placed in the synonymy of L. acutiflora; Leandra atropurpurea in the synonymy of L. australis; Ossaea ramboi in the synonymy of L. catharinensis; Leandra pulchra in the synonymy of L. clidemioides; Leandra furfurella in the synonymy of L. cordigera; Leandra macrosepala in the synonymy of L. laevigata; Leandra dusenii in the synonymy of L. microphylla; Leandra dolichodons in the synonymy of L. penduliflora; Leandra dasytricha and L. mosenii in the synonymy of L. variabilis. We also propose lectotypes for L. australis, L. atropurpurea, L. cordigera, L. dusenii, L. laevigata, and L. pulchra.